THE IMPACT OF EARLY-LIFE GUT MICROBIOTA ON IMMUNE-MEDIATED DISEASES IN CHILDREN – A REVIEW ARTICLE - Gwiaździńska, Oktawia; Strzykała, Anita; Lewandowski, Jakub; Szlegiel, Igor; Myszak, Denis (International Journal of Innovative Technologies in Social Science, 2026)
Background: The gut microbiota plays a crucial role in immune system development, particularly during early life. Increasing evidence suggests its involvement in the pathogenesis of immune-mediated diseases in children. Objective: This review aims to summarize current knowledge on the relationship between early-life gut microbiota composition and the risk of developing asthma, allergic diseases, and Crohn’s disease. Methods: A comprehensive literature review was conducted using PubMed and Google Scholar databases. Keywords included “gut microbiota”, “children”, “asthma”, “allergy”, “Crohn disease”, and “dysbiosis”. Recent clinical studies, systematic reviews, and meta-analyses focusing on pediatric populations were included. Results: Early-life factors such as delivery mode, feeding practices, and antibiotic exposure significantly influence gut microbiota composition. Reduced microbial diversity and dysbiosis were consistently associated with increased risk of asthma, allergies, and inflammatory bowel diseases. Specific bacterial taxa, including reduced Bifidobacterium and increased Proteobacteria, were linked to disease development. Microbial metabolites, particularly short-chain fatty acids, were identified as key modulators of immune responses. Conclusions: Early-life gut microbiota plays a fundamental role in immune programming. Its disruption may increase the risk of immune-mediated diseases. Modulation of microbiota through diet, probiotics, and rational antibiotic use represents a promising preventive and therapeutic strategy.